Childhood Obesity - Ahmad, Qazi Iqbal (Medknow Publications, 2010)
Obesity is increasing at an alarming rate throughout the world. Today it is estimated that there are more than 300 million obese people world-wide. Obesity is a condition of excess body fat often associated with a large number of debilitating and life-threatening disorders. It is still a matter of debate as to how to define obesity in young people. Overweight children have an increased risk of being overweight as adults. Genetics, behavior, and family environment play a role in childhood overweight. Childhood overweight increases the risk for certain medical and psychological conditions. Encourage overweight children to expand high energy activity, minimize low energy activity (screen watching), and develop healthful eating habits. Breast feeding is protective against obesity. Diet restriction is not recommended in very young children. Children are to be watched for gain in height rather than reduction in weight. Weight reduction of less than 10% is a normal variation, not significant in obesity.